Suprasellar haemangioblastoma. Report of two cases and review of the literature - (:unkn) unknown (ELSEVIER SCI LTD, 2005)
We report 2 patients with suprasellar haemangioblastoma (HBL). The first, a 54-year-old man, presented with headache and gradually worsening bilateral visual field defects that had progressed to complete blindness on the right side. Computed tomography (CT) and magnetic resonance imaging (MRI) of the brain demonstrated a suprasellar mass. The mass was removed through a pterional craniotomy. The postoperative course was uneventful. He had no stigmata of von Hippel-Lindau (VHL) disease. After 5 years follow-up, vision in the left eye is normal but the right eye remains blind and MRI reveals no recurrence. The second, a 38-year-old man presented with a 2-month history of severe headaches and complete visual loss in the left eye. He had had surgery for excision of a cerebellar HBL, 5 years prior to this presentation. CT and MRI revealed a residual mass in the posterior fossa and a new suprasellar mass. He underwent craniotomy and subtotal excision of the suprasellar tumour. The histological diagnosis was HBL in both patients. HBL in the sellar and suprasellar region are rare and may be sporadic or occur in association with VHL disease. The literature is reviewed and diagnosis and treatment options discussed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: chiasmal compression; haemangioblastoma; suprasellar; CENTRAL-NERVOUS-SYSTEM; VONHIPPEL-LINDAU DISEASE; STROMAL CELLS; SUPRATENTORIAL HEMANGIOBLASTOMA; INTRASELLAR HEMANGIOBLASTOMA; TUMORS; RADIOSURGERY; EXPRESSION; RESECTION; PATIENT